Back Cover: Superchaotropic Nano‐ion Binding as a Gelation Motif in Cellulose Ether Solutions (Angew. Chem. Int. Ed. 3/2023). Issue 3 (14th December 2022) - Hohenschutz, Max; Bauduin, Pierre; Lopez, Carlos G.; Förster, Beate; Richtering, Walter
Abstract : Synergy between salt and sugar Nanometric ions like Keggin polyoxometalates are revealed to induce the cross‐linking and hydrogel formation of polymeric sugars, namely non‐ionic cellulose ethers, as reported by Max Hohenschutz, Walter Richtering, and co‐workers in their Communication (e202210208) . This novel gelation phenomenon exceeds the thickening effects of typical additives like classical salts and surfactants by orders of magnitude and is due to the superchaotropicity of the nano‐ions, which drives them out of the water bulk onto the polymers.